Pemahaman Kosa Kata dengan Metode Bernyayi Dimadrasah Diniyah Takmiliyah Ula Darussalamah Sadengan Rowotengah - Jalil Mannan, Ahmad Mizan Rosyadi Abdul; Afifah, Nur (UAS PRESS, 2023)
Learning Arabic cannot be separated from understanding vocabulary. Because vocabulary is very urgent in forming a series of sentences. Mastering the understanding of vocabulary really needs enthusiasm and motivation to memorize and understand it quickly and effectively. The singing method is a learning method that focuses on empowering students to learn faster, more effectively, and more fun and can be used in learning vocabulary. Research objectives This is to make it easier to understand vocabulary by developing resources for students and triggering the enthusiasm of Madrasah Dinniyah Takmiliyah Ula Darussalamah students in understanding Arabic vocabulary. The type of research used in this research is a qualitative method. The results of this study conclude that increasing enthusiasm can increase students' effectiveness and memorization in understanding vocabulary and building students' enthusiasm for Arabic